New Visions of outsider Art - Ortega, Inés (Arte, Individuo y Sociedad, 2014)
Recent years have witnessed a growing interest in outsider art. This is not only because works of art located on the fringe of the professional art world serve as aesthetic references for influential contemporary artists but also because, in our opinion, they form part of a much wider movement. Today there is a marked interest in publicizing outsider art and, little by little, these works seem to be abandoning the restricted confines of specialized museums and centers as they conquer new spaces and attract wider audiences. This article analyzes the role of exhibitions in publicizing these works but, more importantly, it studies the underlying theoretical discourse that leads to their consideration as genuine works of art that merit a place in art history. This critical revision has taken place in a series of novel, more or less sound museological narratives on which we will center our attention. We shall consider the recent promotion and dissemination of the pioneering progressive studies from San Francisco Bay Area and the new Museum of Everything located in the United Kingdom, institutions which play a key role in the present dissemination of outsider art.
Keywords: outsider art; exhibitions; museological narratives